Achieving sustainable freshwater systems : (Island Press, 2003)
Achieving Sustainable Freshwater Systems brings together experts from a wide range of disciplines to present key insights and information on sustainable freshwater systems. Contributors represent a variety of perspectives and expertise, helping to illuminate the multiple connections and concerns involved with freshwater systems